Vida-obra de Antonio Gramsci: a política de um filósofo imortalizada na sua literatura-filosofia - Leite, Arthur Damasceno Ribeiro de Oliveira (2016)
This text contains notes coming from the master's research on the life and work of Antonio Gramsci. It intends to demonstrate how the metaphor life-work came to life and how it served to demarcate this variable: exploring the intersection between philosophy, politics and literature in books and in the Prison Letters. The study of translatability and national-popular categories were used as beacons, which helped to understand thought and action, philosophy and politics as translatable aspects of the same phenomenon at the thought of Gramsci, and philosophy translated into policy by the philosophy of praxis as a revolutionary production tool for the underlings, which take the world of consciousness and their condition in the world through it. It is sought to show how the life-work of Gramsci closes the metaphoric border between philosophy, politics and literature: the very philosophy of praxis. It was identified in the work of Gramsci the projection of a historical figure who succeeded in his work and in his life to embody a philosophy, raising it to its most critical moment - cathartic. The text tries to demonstrate how Gramsci's literature constituted production instrument expressed in its interstices the symbolic demarcation of a political subject able to forge in the objective reality the political and cultural phenomenon of the revolutionary historic subject that was opposed frontally to the fascist regime of Mussolini. It is noted that the reciprocal translation of scientific and philosophical languages composes the main plot of his life- work that, woven from the communist world view, it could not stop being questioning and revolutionary of the objective reality that it is intended to be raised to the level of a Nuova civilta comunistica.